Factors Driving Adoption of Humanoid Service Robots in Banks - Lars Hornuf; Maximilian Meiler (CESifo GmbH, 2024)
We examine the technological and socioenvironmental factors influencing the adoption of humanoid service robots in Austrian, German, and Swiss banks. We integrate the technology acceptance model and the technology–organization–environment framework, and employ structural equation modeling to analyze data from the top management of 106 banks. We find that the relative advantage of the innovation, top management support, competitive pressure, and customer acceptance drive the perceived usefulness of humanoid service robots. Moreover, customer acceptance significantly enhances perceived ease of use by the bank. Together, perceived usefulness and perceived ease of use significantly increase banks' intention to adopt humanoid service robots. However, the actual adoption rate of humanoid service robots in banks remains low, indicating the presence of underlying barriers to adoption such as lack of organizational readiness, technical limitations, and regulatory concerns, which are especially relevant for smaller banks with limited resources. Furthermore, some banks perceive humanoid service robots as fascinating novelties rather than essential operational tools. As a result, banks are actively exploring alternatives such as digital avatars, chatbots, and voice bots for certain tasks while continuing to prioritize human-to-human interactions for non-online customer services.
Keywords: L84; O32; O33; 330; humanoid service robots; technology adoption; banking industry